CSC098: Foundation Computing I / Centre of Foundation Studies - UiTM, Centre of Foundation Studies (Universiti Teknologi MARA (UiTM), 2023)
The Foundation Computing I course focuses on the basic knowledge of computer system, the Internet, communication and networking, and general purpose and engineering application softwares in producing Information. This course is designed with a logical progression of topics arranged for students, who are entering tertiary education with different learning styles and varied stages of preparedness to further their studies at higher level. The purpose of this course is to produce students with knowledge of computer technology and problem-solving skills in order to develop long-term retention of principles and practice needed in their future studies. The goal will be accomplished by thorough guidance methods, in-class exercises and hands on exercises. By the end of this course, students are expected to acquire and apply knowledge of computer to respective fields of engineering, medicine, health, environment, agriculture, and industry.